Design, synthesis, structural and molecular characterization, toxicity, psychotropic activity and molecular docking evaluation of a novel phenytoin derivative: 3-decyl-5,5-diphenylimidazolidine-2,4-dione - Guerrab, Walid; El Jemli, Meryem; Akachar, Jihane; Demirtaş, Güneş; Mague, Joel T.; Taoufik, Jamal; Ibrahimi, Azeddine; Ansar, M'Hammed; Alaoui, Katim; Ramli, Youssef (Journal of biomolecular structure & dynamics, 2022)
The hydantoin scaffold is of substantial importance and it is commonly used in drug discovery. Herein, we report the synthesis of a novel phenytoine (a hydantoin derivative) with high yield by the reaction of phenytoin with 1-bromodecyl agent. Namely, 3-decyl-5,5- diphenylimidazolidine-2,4-dione (3DDID). The optimized geometry of the compound was calculated using density functional theory (DFT) method by B3LYP with 6-311++G(d,p) basis set. For this calculation, the X-ray data were used as initial values. Molecular electrostatic potential (MEP) surface and Frontier molecular orbitals (FOMs) were prepared for the compound. The crystal structure of the title compound contains intermolecular N-H···O, C-H···O hydrogen bonds and weak C-H···π interactions. Hirshfeld surface analysis and 2D fingerprint plots of the molecule aid comparison of intermolecular interactions and these analysis reveals that two close contacts are associated with intermolecular hydrogen bonds. The psychotropic activity evaluation of the synthesized compound was further explored using hole bored test for exploratory behaviors, dark//light box test for anxiolytic activity and Rota-road, traction, chimney testes were used to assess the myrelaxant effect. In addition, molecular modeling study was also conducted to rationalize the potential as neurotherapeutic drugs of our synthesized compound by predicting their binding modes, binding affinities and optimal orientation at the active site of the GABA-A receptor and Na + channel. Finally, in silico ADMET predictions was also examined. Highlights Synthesis, structural, and molecular characterization of a novel phenytoin derivative. DFT, XRD, and the Hirshfeld surface analysis of crystal structure was studied. Acute toxicity and psychotropic activity evaluation of 3-decyl-5,5 diphenylimidazolidine-2,4-dione (3DDID). Molecular modeling studies have been conducted to rationalize the obtained data and to determine the probable binding mode. Communicated by Ramaswamy H. Sarma